(3QSGdI aj GdefWbs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s ((3edG Ndjd s)
(3ChdgG (B:s
(3GYde Cf GdOSJhQ Gdebff ai EfTGA cd af Shi GdEdgi gh JbSje GdehVhY Gdcdi s
(3BNQgG (B:s
(3bdGOg GdYde aVdkG Yf GdEbJMGe ai GdJUfja hgh jgOi GdSHjd hdG jfaY bGd hdG bjd Je s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HChdg hbajI HGSe edG YHO Gddg GdYHOdi Ydi ChdGOI jQLY JGQjNgG Edi SfI (B1239 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3eOQSI GdMLjGJ (B_ (3GdehUd (B(115) s
Keywords: (3GdeLGejYs